(untitled) (Malaysian Management Journal, 2016)
The aim of this paper is to analyze whether the worldwide financial crisis integrates the regional markets in Asia more strongly. Secondly, it is also to examine whether the integration of regional markets in Asia necessarily leads to a weak form of market efficiency. To examine this we have considered the different broad based and liquid stock indices such as the Sensex and BSE 100 from the Bombay Stock Exchange; the S&P CNX Nifty from the National Stock Exchange, representing India; the Hang Seng Index from the Hong Kong Stock Exchange, representing China; the Kuala Lumpur Composite Index (KLSE), Bursa Malaysia representing Malaysia; the Nikkei 225 from the Tokyo Stock Exchange representing Japan, and the Straits Times Index (STI) from the Singapore Exchange representing Singapore. The study considered the daily data spanning from 4th January 1994 to 2nd May 2012. The full sample period was split into three forms such as the whole sample, the Global financial crisis and the post global financial crisis. The short term interaction was studied by using Toda Yamamoto’s procedure of Granger’s Causality in VAR Block Exogenity form and the long run equilibrium relationship was tested by applying the Johansen Maximum Likelihood procedure. And so the paper explored the possible, integrating relationship at the volatility level among the regional stock indices by applying the ARCH school of models. Finally, the Random Walk Hypothesis was tested by employing the Chow-Denning (1993) and the Lo and Mackinlay (1988) multiple variance ratio test to examine the efficiency of the market. The major findings of the study indicated that the worldwide financial crisis integrates the regional markets in Asia more strongly in the short term from 2007 onwards. There is no long run equilibrium relationship among the regional stock markets. The study also found that the integration of the financial market does not necessarily contribute to market efficiency.